2003
DOI: 10.1089/152091503763816490
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Information Technology & WebWatch

Abstract: AIDA is a diabetes-computing program freely available from www.2aida.org on the Web. The software is intended to serve as an educational support tool, and can be used by anyone who has an interest in diabetes, whether they be patients, relatives, health-care professionals, or students. In previous "Diabetes Information Technology & WebWatch" columns various indicators of usage of the AIDA program have been reviewed, and various comments from users of the software have been documented. One aspect of AIDA, thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…3,4 To this end, new information technology (IT)-based management systems for diabetes management have been developed and studied. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] We established an interactive, internet-based communication system for patients and medical professionals and demonstrated its short-term efficacy for HbA1c reduction 5 and long-term efficacy for HbA1c reduction and glucose stability. 6 Studies using IT are already increasing and their positive results are found all around the world.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 To this end, new information technology (IT)-based management systems for diabetes management have been developed and studied. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] We established an interactive, internet-based communication system for patients and medical professionals and demonstrated its short-term efficacy for HbA1c reduction 5 and long-term efficacy for HbA1c reduction and glucose stability. 6 Studies using IT are already increasing and their positive results are found all around the world.…”
Section: Introductionmentioning
confidence: 99%